Death-associated protein kinase 1: a double-edged sword in health and disease - Xiuli Zhang; Yehuda G. Assaraf; Yao Lin (Frontiers in Immunology)
Death-associated protein kinase 1 (DAPK1) is a Ca2+/calmodulin-regulated serine/threonine kinase that orchestrates a wide array of cellular activities. It is intricately regulated through multiple mechanisms, including intramolecular signaling and interactions with other proteins, such as kinases and phosphatases. DAPK1 plays a pivotal role in regulating various biological processes, including apoptosis and autophagy, and is implicated in pathogenesis of several disorders, such as cancer, stroke and brain damage, neurodegenerative and within their kinase domains. In 2014, a collection of reviews was cardiovascular diseases, wound healing, kidney injury, and tuberous sclerosis complex. In light of its biological significance, several small molecule modulators of DAPK1 have been developed for therapeutic purposes and as probe compounds to enhance the mechanistic understanding of DAPK1-mediated biological functions. However, the repertoire of available small molecules remains limited, underscoring the need for further research to discover novel strategies for the activation or inhibition of DAPK1. From this perspective, we primarily discuss the structure, biological function, and role of DAPK1 in health and disease, as well as the recently identified small molecule inhibitors and activators. This analysis offers valuable insights for advancing research in the DAPK1 field.